Exploring the science of evacuation behavior and decision-making during large scale community evacuations: A scientometrics analysis and scoping review - Kannangara C; Kuligowski E; Siriwardana C; Zhang G; Adikariwattage V; Jayawardane P (Elsevier Ltd, 2026)
Understanding how people behave during large-scale community evacuations is important as it can reveal key decision-making gaps which can be addressed to improve emergency planning and to keep communities safer. This study examines the critical gaps in existing research on evacuation behavior and decision-making during disasters by holistically exploring the research domain of evacuation behavior. A total of 667 articles and their references were analyzed using scientometrics methods. This study employs a novel approach to the analysis called overlay networks in CiteSpace. The findings highlight gaps in our understanding of human behavior during the evacuation, such as the stay-or-go decision and travel-related behavior, including destination, mode, route, and return-entry choices, in the context of earthquakes, floods, tsunamis, volcanic hazards, and wildfires. Evacuations triggered by technological disasters are explicitly excluded from this review. It also emphasizes that tourist evacuations remain an underexplored area. Also, the current study reveals that established theories, such as the Protective Action Decision Model (PADM) and the Theory of Planned Behavior (TPB), remain underutilized in research on evacuation behavior during hazards like earthquakes, tsunamis, and volcanic eruptions. This research supports the findings of previous studies in emphasizing the need for interdisciplinary approaches to evacuation research. It also underscores the importance of integrating existing behavioral evidence into evacuation models, alongside efforts to collect additional data. Also, the study emphasizes the importance of strengthening research collaborations with scholars in Asia and Africa. This approach seeks to address the disparity in research conducted across different regions of the world.
Keywords: Evacuation; Evacuation behavior; Decision-making; Natural hazards; Disasters